(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-130-138 The article examines the image of childhood in Yu.P. Kazakov’s story “In a dream you cried bitterly” in line with the Chekhov tradition, analyzes the deep connections of the artistic principles of the two writers. The research highlights Yu. P. Kazakov’s interest in Chekhov’s work and similarity of the genre systems of two authors. There have been established the origins of this community, which is determined by the attraction of both A.P. Chekhov and Yu.P. Kazakov to lyrical prose. The author analyzes the features of the Chekhov’s type of narrative with its inherent frivolity and an open ending in the story of Yu.P. Kazakov “In a dream you cried bitterly”. It is proved that Chekhov’s traditions played a significant role in the formation of the topos of childhood in the lyrical prose of Yu.P. Kazakov. Key words: Yu.P. Kazakov, Chekhov’s traditions, the genre of the story, the topos of childhood